2016
DOI: 10.1002/2016jd024859
|View full text |Cite
|
Sign up to set email alerts
|

An enhanced VIIRS aerosol optical thickness (AOT) retrieval algorithm over land using a global surface reflectance ratio database

Abstract: The Visible/Infrared Imager Radiometer Suite (VIIRS) on board the Suomi National Polar‐orbiting Partnership (S‐NPP) satellite has been retrieving aerosol optical thickness (AOT), operationally and globally, over ocean and land since shortly after S‐NPP launch in 2011. However, the current operational VIIRS AOT retrieval algorithm over land has two limitations in its assumptions for land surfaces: (1) it only retrieves AOT over the dark surfaces and (2) it assumes that the global surface reflectance ratios betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
47
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 38 publications
(53 reference statements)
0
47
0
Order By: Relevance
“…To date, PMB has been used by federal and state epidemiologists completing EPHT projects in different parts of the US [16,18,22,26].Within this decade, the availability and use of satellite AOD data have become more routine [6,16,[27][28][29][30][31]. Newer generation satellite instruments measure AOD with increased temporal accuracy and finer spatial resolution [27,[32][33][34][35][36][37]. AOD is a unitless measure of the scattering and absorption of visible light by aerosols (particles) in the atmosphere [38][39][40].…”
mentioning
confidence: 99%
“…To date, PMB has been used by federal and state epidemiologists completing EPHT projects in different parts of the US [16,18,22,26].Within this decade, the availability and use of satellite AOD data have become more routine [6,16,[27][28][29][30][31]. Newer generation satellite instruments measure AOD with increased temporal accuracy and finer spatial resolution [27,[32][33][34][35][36][37]. AOD is a unitless measure of the scattering and absorption of visible light by aerosols (particles) in the atmosphere [38][39][40].…”
mentioning
confidence: 99%
“…For the weighting factor, e ‐folding lengths of 500 km for longitude and 250 km for latitude are used (to account for prevailing zonal winds over the globe). It was found that the background AOD from AERONET can be accurately interpolated regardless of the e‐folding length in the range of 100–1000 km [ Zhang et al ., ], although the error can increase over areas where AERONET sites are sparsely distributed. It should be noted that the single channel retrieval of AVHRR leads us to using a seasonal aerosol optical model in each geographic region rather than retrieving it in each pixel, such that extrapolation of AOD using the optical models is not optimal.…”
Section: Descriptions Of Avhrr Aerosol Retrieval Algorithmmentioning
confidence: 99%
“…Satellite remote sensing, as the most direct and effective way to capture the spatial distributions and temporal variations of aerosols over large regions, has been widely used for researches at the local and global scales compared with ground-based Sun photometers (Garcia et al, 2016;Kahn, 2013;Kokhanovsky et al, 2007;Li et al, 2005;Noh et al, 2009;Qin et al, 2016;Sun et al, 2016;Veefkind et al, 1999;Zheng et al, 2017). During past 20 years, a series of sensors have been launched and used in aerosol related researches over land and ocean, such as National Oceanic and Atmospheric Administration Advanced Very High Resolution Radiometer (Geogdzhayev et al, 2004;Hsu et al, 2017), Multi-angle Imaging SpectroRadiometer (Diner et al, 2005;Limbacher & Kahn, 2017), Advanced Along Track Scanning Radiometer (Grey et al, 2006;Guo et al, 2009;Mei et al, 2013;Xue et al, 2009), Polarization and Directionality of the Earth's Reflectance (Deuze et al, 2001), Sea-Viewing Wide Field-Of-View Sensor (Melin et al, 2007;Sayer et al, 2012), Landsat Operational Land Imager (Tian et al, 2018), MODIS (MODerate-Resolution Imaging Spectroradiometer; Levy et al, 2007), VIIRS (Visible Infrared Imaging Radiometer Suite; Jackson et al, 2013;Su et al, 2015;Zhang et al, 2016), and Chinese FengYun Medium Resolution Spectral Imager (Han et al, 2015;Tong et al, 2011). One of the main challenges for the AOD retrieval using satellites is to isolate aerosol particle scattering contributions from satellite recorded signals, which is the superposition of atmospheric path reflectance including atmospheric molecules and aerosol matters as well as surface reflectance signals .…”
Section: Introductionmentioning
confidence: 99%